Pelaksanaan Kebijakan Pembebasan Narapidana di Masa Pandemi Covid-19 di Lapas Kerobokan Denpasar - I Gede Gita Ananda Putra; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2022)
The Minister's decision caused the assimilation of up to 167 people in the head of the family in Indonesia. The public considers that the steps that have been taken by the government are not sufficient to reduce the spread of Covid-19, the community is of the opinion that inmates can live better and more comfortably in prisons if they carry out social distancing programs (physical distancing) together with complete control mechanisms. Not only that, public concern and anxiety will increase if prisoners who receive the Assimilation Rights Program repeat their crimes. The aims of this research are to discuss the requirements and factors that are used as the basis for the release of prisoners in Kerobokan Prison and what obstacles arise in the Implementation of Assimilation in Rutan IIA Kerobokan. This research method is empirical research using a sociological juridical approach. There are 3 sources of research material, namely primary, secondary and tertiary sources. The techniques used to collect data are library study techniques and interview techniques. The results of this study explain that in the implementation of the assimilation permit at the Class IIA Kerobokan Prison, this has been stated in the Regulation of the Minister of Law and Human Rights based on the Minister of Law and Human Rights Number 10 of 2020 and amended in the Minister of Law and Human Rights Number 32 of 2020 concerning Terms and Conditions The method of granting has been refined to become digestion, probation, no early leave, and pre-compulsory leave for applications and children in avoiding and controlling the covid19 pandemic, as well as obstacles encountered, one of which was having passed half the penalty time.